The Effect of Sarcopenia on Outcomes in Geriatric Blunt Trauma. Issue 11 (November 2017) - Malekpour, Mahdi; Bridgham, Kelly; Jaap, Kathryn; Erwin, Ryan; Widom, Kenneth; Rapp, Megan; Leonard, Diane; Baro, Susan; Dove, James; Hunsinger, Marie; Blansfield, Joseph; Shabahang, Mohsen; et al.
Elderly patients are at a higher risk of morbidity and mortality after trauma, which is reflected through higher frailty indices. Data collection using existing frailty indices is often not possible because of brain injury, dementia, or inability to communicate with the patient. Sarcopenia is a reliable objective measure for frailty that can be readily assessed in CT imaging. In this study, we aimed to evaluate the effect of sarcopenia on the outcomes of geriatric blunt trauma patients. Left psoas area (LPA) was measured at the level of the third lumbar vertebra on the axial CT images. LPA was normalized for height (LPA mm 2 /m 2 ) and after stratification by gender, sarcopenia was defined as LPA measurements in the lowest quartile. A total of 1175 patients consisting of 597 males and 578 females were studied. LPAs below 242.6 mm 2 /m 2 in males and below 187.8 mm 2 /m 2 in females were considered to be sarcopenic. We found sarcopenia in 149 males and 145 females. In multivariate analysis, sarcopenia was associated with a higher risk of in-hospital mortality (odds ratio [OR]: 1.61, 95% confidence interval [CI]: 1.01–2.56) and a higher risk of discharge to less favorable destinations (OR: 1.42, 95% CI: 1.05–1.97). Lastly, sarcopenic patients had an increased risk of prolonged hospitalization (hazard ratio: 1.21, 95% CI: 1.04–1.40).